2019
DOI: 10.1111/jvh.13069
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐free therapy as the cause of white matter tracts and cerebral perfusion recovery in patients with chronic hepatitis C

Abstract: Additional supporting information may be found online in the Supporting Information section at the end of the article. How to cite this article: Bladowska J, Pawłowski T, Fleischer-Stępniewska K, et al. Interferon-free therapy as the cause of white matter tracts and cerebral perfusion recovery in patients with chronic hepatitis C. J Viral Hepat. 2019;26:635-643. https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…DTI and PWI studies in this group also revealed greater anisotropy after therapy in several association, commissural and projection tracts and lower diffusivity in several association and projection tracts that correlated with changes in the neuropsychological profile. Higher basal ganglia perfusion after therapy was also observed, but this finding did not correlate with other neuropsychiatric and DTI changes [25]. In a pilot study, improvement of working memory, visual and verbal memory and executive function after treatment with ledipasvir-sofosbuvir correlated with several inflammatory biomarkers in peripheral blood, such as tumor necrosis factor-α, IFN-γ and catechol-O-methyl-transferase [80].…”
Section: Direct-acting Antiviral Agents (Daa)mentioning
confidence: 89%
See 2 more Smart Citations
“…DTI and PWI studies in this group also revealed greater anisotropy after therapy in several association, commissural and projection tracts and lower diffusivity in several association and projection tracts that correlated with changes in the neuropsychological profile. Higher basal ganglia perfusion after therapy was also observed, but this finding did not correlate with other neuropsychiatric and DTI changes [25]. In a pilot study, improvement of working memory, visual and verbal memory and executive function after treatment with ledipasvir-sofosbuvir correlated with several inflammatory biomarkers in peripheral blood, such as tumor necrosis factor-α, IFN-γ and catechol-O-methyl-transferase [80].…”
Section: Direct-acting Antiviral Agents (Daa)mentioning
confidence: 89%
“…18 FDG-PET-Cortical anterior > posterior and cerebellar hypometabolism [17] 11 C-(R)-PK-11195-PET-Basal ganglia and thalamic microglial activation [18,19] 123 I-CIT-SPECT-Decreased dopaminergic and serotoninergic innervation [17,20] IFN-α Decreased anterior metabolism on 18 FDG-PET [21] Inhibited dopamine release in ventral striatum [22] No effect on serotoninergic innervation [23] PWI Cortical anterior > posterior reduced perfusion [24] Increased basal ganglia perfusion [24] DAA Increased basal ganglia perfusion [25]…”
Section: Nuclear Medicine Response To Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Bladowska et al used magnetic resonance diffusion tensor and perfusion weighted imaging of white matter tracts to demonstrate significant changes in the microstructure and perfusion after DAA induced HCV eradication. This was believed to indicate white matter recovery 35 . On the functional level, Kleefeld et al found cognitive function improvement in visual memory/learning, executive functions, verbal fluency, processing speed and motor skills but not in verbal learning and attention/working memory after DAA treatment 36 …”
Section: Discussionmentioning
confidence: 99%
“…The direct-acting antiviral agents (DAAs) are a set of medications used to treat patients infected by the HCV. The summary of study characteristics and quality assessment of the 12 [29][30][31][32][33][34][35][36][37][38][39][40] included studies are presented in Table 2. Two of them were considered high quality, whilst the remaining ten others had ratings ranging from 4 to 6 stars, suggesting moderate quality.…”
Section: Significance Statementmentioning
confidence: 99%